4w+48=-2(w-9)

Simple and best practice solution for 4w+48=-2(w-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w+48=-2(w-9) equation:


Simplifying
4w + 48 = -2(w + -9)

Reorder the terms:
48 + 4w = -2(w + -9)

Reorder the terms:
48 + 4w = -2(-9 + w)
48 + 4w = (-9 * -2 + w * -2)
48 + 4w = (18 + -2w)

Solving
48 + 4w = 18 + -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
48 + 4w + 2w = 18 + -2w + 2w

Combine like terms: 4w + 2w = 6w
48 + 6w = 18 + -2w + 2w

Combine like terms: -2w + 2w = 0
48 + 6w = 18 + 0
48 + 6w = 18

Add '-48' to each side of the equation.
48 + -48 + 6w = 18 + -48

Combine like terms: 48 + -48 = 0
0 + 6w = 18 + -48
6w = 18 + -48

Combine like terms: 18 + -48 = -30
6w = -30

Divide each side by '6'.
w = -5

Simplifying
w = -5

See similar equations:

| -10.5-9.7=2w+1.4-1w | | 3(x+8)=63 | | 5p-4p+2p+3=12 | | 9^3X-1=1/27 | | 8t=-8 | | x^3+x=500 | | -10h=-20 | | 2/12=6/x | | 15w+-19w=-16 | | W/2-3^12 | | tg(-x)=1-2tg(x) | | cos(240)= | | x(13+x)=0 | | (3-i)(x-iy)=3-11i | | x+y=1.70 | | 12(x-4)-8(2x-7)=3(x+5) | | 3+10x=0.5 | | 7(v-4)=3v-4 | | 11x-54-8x-12=7x+30-6x | | 5u-43=9(u-7) | | 2(u+7)=-2u+30 | | 1.1(-0.3w+10)=7.7 | | 3=3(v+5)+3v | | p=2(3)+2(4) | | -6x+4(x-8)=-24 | | -4(3y)-5+3(5y+5)= | | -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 | | 12/2=6/x | | -19-4+28-35=-6-2m-5+3m | | 8/9(b-1/4)=2/3 |

Equations solver categories